2021
DOI: 10.1007/s00259-021-05192-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of APOE-ε2 and APOE-ε4 alleles with PET-measured amyloid-β and tau deposition in older individuals without dementia

Abstract: Purpose To examine associations between the APOE-ε2 and APOE-ε4 alleles and core Alzheimer’s disease (AD) pathological hallmarks as measured by amyloid-β (Aβ) and tau PET in older individuals without dementia. Methods We analyzed data from 462 ADNI participants without dementia who underwent Aβ ([18F]florbetapir or [18F]florbetaben) and tau ([18F]flortaucipir) PET, structural MRI, and cognitive testing. Employing APOE-ε3 homozygotes as the reference group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 86 publications
3
34
2
Order By: Relevance
“…Together, these results suggest that only one APOE ε4 allele is sufficient to increase tau accumulation in females, while two APOE ε4 alleles are needed to cause a similar effect in males. Consistent with previous studies, 29 , 30 we found that region of interest analysis of entorhinal cortex, amygdala and parahippocampal gyrus showed an amyloid-β-independent association between the APOE ε4 gene dosage and tau deposition in males but not females after controlling for global cortex 18 F-florbetapir SUVR. These findings have important clinical implications towards developing sex and genotype-guided therapeutics in Alzheimer’s disease and uncover a possible explanation underlying differential APOE ε4-associated Alzheimer’s risk in males and females.…”
Section: Discussionsupporting
confidence: 92%
“…Together, these results suggest that only one APOE ε4 allele is sufficient to increase tau accumulation in females, while two APOE ε4 alleles are needed to cause a similar effect in males. Consistent with previous studies, 29 , 30 we found that region of interest analysis of entorhinal cortex, amygdala and parahippocampal gyrus showed an amyloid-β-independent association between the APOE ε4 gene dosage and tau deposition in males but not females after controlling for global cortex 18 F-florbetapir SUVR. These findings have important clinical implications towards developing sex and genotype-guided therapeutics in Alzheimer’s disease and uncover a possible explanation underlying differential APOE ε4-associated Alzheimer’s risk in males and females.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, our results suggest that APOE-ε4, by exacerbating cortical Aβ deposition in MTL areas, might facilitate the spread of tau in extra medial-temporal regions, plausibly promoting an earlier co-localization of Aβ and tau. In line with this, previous PET imaging studies have documented a higher tau deposition in APOE-ε4 carrier AD patients compared to noncarriers [29,[36][37][38]. Furthermore, our interaction effects may help to explain the faster disease progression [39][40][41] as well as the stronger relationship between Aβ and cognitive decline [42,43] in APOE-ε4 carriers compared to non-carriers.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in the Aβ+ individuals we observed a cross-talk between PGS and baseline levels of amyloid-PET on the rate of subsequent change in tau-PET, suggesting that the PGS affects the formation of tau pathology in cortical brain regions downstream of the abnormally elevated Aβ. In contrast, previous studies on APOE ε4 status reported that the effect of APOE ε4 on higher cortical tau-PET accumulation were due to the effect on increased levels of Aβ [45][46][47] .…”
Section: Discussioncontrasting
confidence: 70%